2013
DOI: 10.2337/db13-0696
|View full text |Cite
|
Sign up to set email alerts
|

A 5-Day High-Fat, High-Calorie Diet Impairs Insulin Sensitivity in Healthy, Young South Asian Men but Not in Caucasian Men

Abstract: South Asians (SAs) develop type 2 diabetes at a younger age and lower BMI compared with Caucasians (Cs). The underlying cause is still poorly understood but might result from an innate inability to adapt to the Westernized diet. This study aimed to compare the metabolic adaptation to a high-fat, high-calorie (HFHC) diet between both ethnicities. Twelve healthy, young lean male SAs and 12 matched Cs underwent a two-step hyperinsulinemic-euglycemic clamp with skeletal muscle biopsies and indirect calorimetry bef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
75
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(77 citation statements)
references
References 49 publications
(76 reference statements)
1
75
1
Order By: Relevance
“…Normal acute-phase insulin release to glucose and intact -cell function support the observation that chronic hyperinsulinemia is mainly driven by impaired insulin clearance in Cc1 / mutants (15). Studies in mice (17), dogs (18), and humans (19) demonstrated that defective hepatic insulin clearance is involved in diet-induced insulin resistance. Providing a Western-style diet caused rapid hepatic insulin resistance in healthy young South Asian men but not Caucasians, in association with altered insulin clearance in the Asian group (19).…”
Section: Ex Vivo Palmitate Oxidationmentioning
confidence: 73%
See 1 more Smart Citation
“…Normal acute-phase insulin release to glucose and intact -cell function support the observation that chronic hyperinsulinemia is mainly driven by impaired insulin clearance in Cc1 / mutants (15). Studies in mice (17), dogs (18), and humans (19) demonstrated that defective hepatic insulin clearance is involved in diet-induced insulin resistance. Providing a Western-style diet caused rapid hepatic insulin resistance in healthy young South Asian men but not Caucasians, in association with altered insulin clearance in the Asian group (19).…”
Section: Ex Vivo Palmitate Oxidationmentioning
confidence: 73%
“…Studies in mice (17), dogs (18), and humans (19) demonstrated that defective hepatic insulin clearance is involved in diet-induced insulin resistance. Providing a Western-style diet caused rapid hepatic insulin resistance in healthy young South Asian men but not Caucasians, in association with altered insulin clearance in the Asian group (19). We have shown that high fat (HF) reduced hepatic CEACAM1 level by >60% and impaired insulin clearance in WT mice within 3 weeks to introduce metabolic abnormalities that were prevented by forced transgenic fat-inducible CEACAM1 overexpression in liver (17).…”
Section: Ex Vivo Palmitate Oxidationmentioning
confidence: 99%
“…Although lipids can be effective ligands for PXR and CAR, and therefore, one could expect upregulation of drug metabolism by increased lipid intake; in this study, we have demonstrated that a short-term hypercaloric HFD decreases drug metabolism. The increased lipid exposure in healthy volunteers induces hepatic accumulation of triglycerides, [12,15] which also involves an increase in the release of inflammatory cytokines such as tumor necrosis factor and interleukin-6. [16,17] Because an increase in these cytokines is associated with downregulation of P450 enzyme activity, [18] one may speculate that such an inflammatory response might be involved in the decreased activity of CYP3A4 and CYP2C19.…”
Section: Discussionmentioning
confidence: 99%
“…Abdominal fat depots were quantified with turbo spin echo MRI using a 1.5 T whole-body MRI scanner (Gyroscan ACS-NT15, Philips, Best, the Netherlands) in the postprandial state [14], and hepatic triacylglycerol content was assessed by proton MR spectroscopy [15], as described previously [16].…”
Section: Mr Studiesmentioning
confidence: 99%
“…Participants underwent anthropometric measurements, a 7 h two-step hyperinsulinaemic-euglycaemic clamp with stable isotopes, skeletal muscle biopsies and indirect calorimetry after an overnight fast, as described previously [16]. Body fat mass and lean body mass (LBM) were assessed by bioelectrical impedance analysis (Bodystat 1500, Bodystat, Douglas, Isle of Man, UK).…”
Section: Metabolic Studiesmentioning
confidence: 99%